2021
DOI: 10.1021/acsomega.1c01994
|View full text |Cite
|
Sign up to set email alerts
|

Impact of H2O on the Adsorption of Hg0 on Activated Carbon

Abstract: In this work, the influence of water on the adsorption of mercury is systematically investigated on basic and washed activated carbons. Breakthrough curves were measured and temperature-programmed desorption (TPD) experiments were performed with mercury and water. Both physisorptive and chemisorptive interactions are relevant in the adsorption of mercury. The experiments show that the presence of water in the pores promotes chemisorption of mercury on washed activated carbons while there is little influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(65 reference statements)
2
5
0
Order By: Relevance
“…This mechanism has been proposed in a previous publication and could also provide a small contribution to chemisorption of mercury in other modified materials. Compared to the loadings found in this work, the loadings described in ref . are significantly lower.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…This mechanism has been proposed in a previous publication and could also provide a small contribution to chemisorption of mercury in other modified materials. Compared to the loadings found in this work, the loadings described in ref . are significantly lower.…”
Section: Resultssupporting
confidence: 54%
“…It is suggested that the increase in capacity here is due to an accumulation of mercury on oxygen functional groups formed or exposed during modification of the carbons. This mechanism has been proposed in a previous publication 27 and could also provide a small contribution to chemisorption of mercury in other modified materials. Compared to the loadings found in this work, the loadings described in ref.…”
Section: ■ Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In a previous publication, 25 we have investigated the coadsorption of mercury and water. It was shown, among other things, that adsorbed water on the surface of the activated carbon only leads to an increase in the chemisorption of Hg 0 in the presence of functional oxygen groups on the surface of the activated carbon.…”
Section: Introductionmentioning
confidence: 99%